STUDENTS' VIEWS ON EDUCATIONAL REFORM: THE TYRANNY OF WORK - Goldenberg, Marsha (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1968)
Our system of education emphasizes that a "work!" atmosphere allows students to plow through 239 pages of Geography and Mathematics and History Text Books. The pupils then learn to "memorize!" this vast amount of data, which they do not fully understand, in order to recite the correct answers back to their teachers. "Study!" is necessary for the inevitable examinations and report cards which dictate whether a pupil remains for a second time or is allowed to pass into the next grade.